Quantitating active photosystem II reaction center content from fluorescence induction transients - Murphy, Cole D.; Ni, Guangyan; Li, Gang; Barnett, Audrey; Xu, Kui; Grant-Burt, Jessica; Liefer, Justin D.; Suggett, David J.; Campbell, Douglas A. (Limnology and Oceanography: Methods, 2017)
Photosystem II (PSII) is a pigment-protein complex that photochemically extracts electrons from water, generating the reductant that supports biological productivity in all biomes. Estimating the content of active PSII reaction centers in a liquid sample is a key input for estimating aquatic photosynthesis rates, as well as for analyzing phytoplankton stress responses. Established procedures for PSII content quantification based on oxygen evolution are slow, imprecise and require dense cell suspensions, and are thus inapplicable to many laboratory or field studies. A new approach uses baseline chlorophyll fluorescence emission divided by the effective absorbance cross section for PSII photochemistry, with both variables derivable from single turnover fluorescence induction protocols. This approach has not been widely tested and is potentially subject to variation in samples suffering progressive photoinactivation or induction of non-photochemical quenching under variable light. We evaluated the validity of this approach for a marine picocyanobacteria, low and high light Prochlorococcus ecotypes, arctic and temperate prasinophyte green alga and two centric diatoms, generating 209 paired determinations from a range of growth and treatment conditions. We successfully calibrated the fluorescence derived estimator for PSII reaction center content, and demonstrate a modification that corrects for the short term influence of photoinactivation. The modified parameter shows little response to induction of non-photochemical quenching. In doing so we show the potential and limitations of an estimator of active PSII reaction center content that is sufficiently robust to support rapid, time-resolved autonomous measures of primary productivity from lakes and oceans.